PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL BERBASIS ETNOSAINS JAYAPURA PADA SISWA SMP - Hutahaean, Jan; Risamasu, Putu Victoria M (Charm Sains: Jurnal Pendidikan Fisika, 2025)
A study has been conducted on the application of the Contextual Teaching and Learning learning model based on Jayapura ethnoscience and its influence on students' interest in learning science and mastery of science concepts. The research model used is a quantitative research type with Quasi Experimental design with a nonequivalent control group design type. The population in this study were all students of class VII at SMP Negeri 13 Jayapura, and the sample was class VII A and VII B. The instruments used were questionnaire instruments and science learning outcome evaluation instruments. Data analysis used regression analysis using SPSS 23 and N-Gain analysis The results of the study showed that there was an influence of the application of the CTL learning model based on Jayapura ethnoscience on students' interest in learning science with a significance value of 0.001. Furthermore, it was found that the application of the Jayapura ethnoscience-based CTL model was proven to increase students' mastery of concepts in the material on the structure and layers of the earth, an increase in N-gain of 0.62 (medium category) was found in the experimental group, higher than in the control class with an N-gain of 0.13 (low category).